2022
DOI: 10.2174/1570159x20999220131163504
|View full text |Cite
|
Sign up to set email alerts
|

Transient Opening of the Blood-Brain Barrier by Vasoactive Peptides to Increase CNS Drug Delivery: Reality Versus Wishful Thinking?

Abstract: Background: The blood-brain barrier inhibits the central nervous system penetration of 98% of small molecule drugs and virtually all biologic agents, which has limited progress in the treatment of neurologic disease. Vasoactive peptides have been shown in animal studies to transiently disrupt the blood-brain barrier and regadenoson is currently being studied in humans to determine if it can improve drug delivery to the brain. However, there are many other vasoactive peptides that could potentially be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 154 publications
(275 reference statements)
0
4
0
Order By: Relevance
“…The inclusion criteria were the same as for the epilepsy group. Because medication can affect BBB permeability in two ways (disruptive and restorative) 20,32 and may cause memory deficits, 33 medication taken by individuals in this study were ascertained. The study was approved by the local institutional review board, and all people participating gave written informed consent.…”
Section: Key Pointsmentioning
confidence: 99%
“…The inclusion criteria were the same as for the epilepsy group. Because medication can affect BBB permeability in two ways (disruptive and restorative) 20,32 and may cause memory deficits, 33 medication taken by individuals in this study were ascertained. The study was approved by the local institutional review board, and all people participating gave written informed consent.…”
Section: Key Pointsmentioning
confidence: 99%
“…Alternative mechanisms to BBB crossing can see both peptide‐mediated direct translocation, typical of cell‐penetrating peptides (CPPs), and transient disruption of the tight junctions between endothelial cells of the BBB. These BBB‐opening properties are shown in some peptide analogs of bradykinin, and can be exploited to improve the delivery of anticancer drugs to the brain 66,67 . Moreover, in general, the direct translocation of CPPs is typically triggered by the interaction between positively charged CPP residues and negatively charged membrane elements, causing either permanent or temporary membrane instability induced by the folding of the lipid membrane.…”
Section: Innovative Tracers Capable Of Crossing the Bbbmentioning
confidence: 99%
“…These BBB‐opening properties are shown in some peptide analogs of bradykinin, and can be exploited to improve the delivery of anticancer drugs to the brain. 66 , 67 Moreover, in general, the direct translocation of CPPs is typically triggered by the interaction between positively charged CPP residues and negatively charged membrane elements, causing either permanent or temporary membrane instability induced by the folding of the lipid membrane. Several mechanistic models for direct penetration have been proposed, as extensively reviewed elsewhere.…”
Section: Innovative Tracers Capable Of Crossing the Bbbmentioning
confidence: 99%
“…While blocking toxins, the BBB can also prevent many drugs from reaching the nervous system. It has been reported that 98% of small-molecule drugs cannot cross the BBB and act on the nervous system ( Neumaier et al, 2021 ; Smith-Cohn et al, 2022 ). Moreover, the processing mechanisms for natural medicine make it difficult for the drug to pass through the BBB, and these drugs have low solubility in brain tissue ( Zhang J. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%